(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Susceptibility of P. interpunctella and L. serricorne in airtight package containing coffee has been evaluated in presence of protective atmosphere with pressurized nitrogen and carbon dioxide (0.2-0.4 bar). In each jar, previously filled with coffee (250 g) 2 cylindrical containers (0 3.7 cm; h 5.5 cm) in plastic rigid transparent material were placed centrally, closed by a lid in soft plastic, with a rectangular opening, protected by a wire net to permit the content to be aired; in each container containing artificial substrate and coffee individuals of the same stage and species were placed. On the whole P. interpunctella individuals show a longer survival on artificial diet. II-III and IV instar larvae of P. interpunctella are the least sensitive stage, as 6 days are required to obtain 100% mortality. L. serricorne resulted to be very susceptible to nitrogen and carbon dioxide atmosphere; 100% mortality occurs after 24 hours from the packaging for both diets. Eggs are the most resistant stage as no egg hatching is observed after a stay of 7 and 8 days in nitrogen atmosphere respectively on coffee and artificial diet.